THE DIFFERENCE BETWEEN THE JIGSAW LEARNING MODEL AND DIRECTED INQUIRY ACTIVITIES ON THE READING COMPREHENSION ABILITY OF FIFTH GRADE STUDENTS AT NURUWE CHRISTIAN ELEMENTARY SCHOOL - Semuel Matital; Henny Dewi Koeswanti (PIONIR: JURNAL PENDIDIKAN, 2025)
This study aims to determine the differences between the Jigsaw and Directed Inquiry Activity (DIA) learning models on the reading comprehension ability of fifth-grade students at Nuruwe Christian Elementary School. The purpose of this study is to improve students' reading comprehension ability. This study used a quantitative experimental questionnaire method with a nonequivalent control group design, involving 56 students in classes VA and VB (VA 28 students in the control class using Jigsaw and VB 28 students in the experimental class using Directed Inquiry Activity). Data were collected through essay-based test questions, pretest and posttest data were analyzed using a t-test. The results showed a significant increase in both groups: the reading comprehension ability of students in the control class (Jigsaw) experienced an average increase from 78.75 to 87.86, while the experimental class (DIA) from 78.39 to 86.79. Meanwhile, the t-test analysis revealed a stronger difference in DIA (t-test value -14.517) compared to Jigsaw (t-test value -9.500). The study's conclusions confirm that both models have a positive impact, but DIA is superior due to its independent investigation learning design with 5W+1H questions, thus not only training literal comprehension but also developing critical thinking skills.The research implications recommend the application of DIA to improve students' reading comprehension skills. Keywords: Reading Comprehension, Jigsaw Learning Model, Directed Inquiry Activity Learning Model